2022
DOI: 10.1038/s41598-022-10142-x
|View full text |Cite
|
Sign up to set email alerts
|

Learned self-regulation in top-level managers through neurobiofeedback training improves decision making under stress

Abstract: Top-level management teams are particularly exposed to stress factors as they frequently have to make important decision under stress. While an existing body of research evidence suggests that stress negatively affects decision-making processes, very little is known about possible strategies to reduce these negative effects. The aim of the current work is to investigate the effect of training self-regulation ability through neurobiofeedback on managers’ intertemporal and risky decision making. Twenty-three man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 73 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Data analysis was carried out considering intra-individual variations of physiological parameters (i.e., metabolism level) and within the same evaluation session (i.e., hydration), in the stress and recovery phases (Time).First, normalization of all dependent variables was conducted. Subsequently, baseline amplitude was calculated over 2 min rest data recording to provide an indication of the ongoing rest activity (Iodice et al, 2022). The main metric used for presenting the e cacy of self-regulation is Delta calculated between the mean of the baseline and peak values of physiological parameters during both stress tasks and recovery periods during the assessment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data analysis was carried out considering intra-individual variations of physiological parameters (i.e., metabolism level) and within the same evaluation session (i.e., hydration), in the stress and recovery phases (Time).First, normalization of all dependent variables was conducted. Subsequently, baseline amplitude was calculated over 2 min rest data recording to provide an indication of the ongoing rest activity (Iodice et al, 2022). The main metric used for presenting the e cacy of self-regulation is Delta calculated between the mean of the baseline and peak values of physiological parameters during both stress tasks and recovery periods during the assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, some authors have associated this capacity with the concept of psychological resilience: an indicator of the ability to cope and deal with possible adverse situations (Fletcher & Hanton, 2003;Iodice et al, 2022). Given the pervasiveness of the stress response and its documented negative in uences on both short-and long-term health outcomes, as well as a multitude of individual abilities (O'Connor et al, 2021; Thoits, 2010) and performances (Anderson et al, 2019;Lochbaum et al, 2022) including the negative phenomenological cost (Arnold & Fletcher, 2021), an e cient stress management through selfregulation represents a highly desirable ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtained discounting parameters were then log-transformed to ensure normality as based on literature (e.g., Calluso et al, 2020 ; Cannito et al, 2021 ; Iodice et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that such a state is achieved through an efficient mind–body regulation, underlined by an adaptive interplay between sympathetic and parasympathetic nervous subsystems ( Benarroch et al, 1995 ; Porges, 2007 ; Thayer and Lane, 2009 ). Recently, some authors have indicated that the efficiency of self-regulation is largely dependent on resilience, a key psychobiological capacity for maintaining normal functioning and health that involves adaptability to adversity ( Fletcher and Hanton, 2003 ; Russo et al, 2012 ; Iodice et al, 2022 ). This theoretical framework is based on the neurovisceral integration model, which synthesizes extensive evidence linking the autonomic and central nervous systems in a functional and structural network involved in the emotional regulation of behaviour ( Dworkin et al, 1994 ; Porges, 2007 ; Thayer and Lane, 2009 ; Pezzulo et al, 2018 ; Iodice et al, 2019 ; Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%